Financial Inclusion, Community Capacity Building and Pro-Wildlife Conservation Behavior around the Northern Periphery of Dja Biosphere Reserve, Cameroon - Nashipu Thalut; Dobdinga Cletus Fonchamnyo; Molem Christopher Sama (Publisher of Widyagama University of Malang (UWG Press), 2020)
The study examines the contribution of financial inclusion and community capacity building on pro-wildlife conservation behavior among rural households at the Northern Periphery of Dja Biosphere Reserve, the east region of Cameroon. The data were elicited through the survey questionnaire administered on a sample of 279 households involved in the program of conservation in the areas. The study used a cluster sampling approach in grouping proximity villages into four zones and a purposive sampling technique was used in selecting the households. The objective was achieved empirically using three-stage maximum likelihood estimation techniques; factor analysis, confirmatory factor analysis and structural equation modeling. The result shows that financial inclusion and community capacity building had a significant positive effect on pro-wildlife conservation behavior. The magnitude of the effect of financial inclusion on pro-wildlife conservation behavior was even larger than the magnitude of the effect of community capacity building. The findings suggest that financial inclusion and community capacity building had the tendency to reduce the decline in wildlife stocks as it promoted friendly behavior towards wildlife and its habitats. The study, therefore, recommends policies that support financial inclusion and community capacity building that are essential for sustainable conservation since it promotes pro-wildlife conservation behavior.JEL Classification: G20, O15, Q57